A Study on Satisfaction Level of Betel Leaf Farmers in Tamil Nadu with Reference to Karur District - Kathirvel, N. (Indian Journal of Marketing, 2011)
This article focuses on history of customer loyalty, its impact on marketing, and also the influence of various factors on customer loyalty. More importantly, the article analyses the customer satisfaction, customer value and customer loyalty so as to identify the market segments based on loyalty and value factors rather than only on economic factors. The article also focuses on the classification of customers on the basis of loyalty. The typical customer loyalty programs used by the companies are also discussed in the article. Agriculture, which is considered the backbone of the Indian economy, has taken a back seat due to the apathy of government policies in the last two decades. The percentage of cultivable land has come down. Meanwhile, nearly 70 percent of the population depending upon agriculture for their daily livelihood directly or indirectly, is currently undergoing a transformation. The economic development of a country depends on the development of the core industry in which the majority of its people have been engaged for quite a long time. The Indian economy has been largely based on agriculture from time immemorial. Multi-stage stratified random sampling has been adopted for the present study with Karur District as the universe, the taluk as the stratum, the village as the primary unit of sampling and the betel leaf farmers as the ultimate unit. Primary data required for the study were collected from the 500 selected respondents of Karur district in order to analyze the technical efficiency of the farmers. The field survey was carried out during the period from April 2009 to August 2009 to collect the primary data. The descriptive Statistics-Percentages, mean, standard deviation and scaling technique were used for preliminary analysis of data.